World Bank East Asia and Pacific Economic Update, April 2015 : Adjusting to a Changing World - World Bank (Washington, DC, 2015)
The East Asia and Pacific Economic Update provides regular, biannual analyses of development trends and economic policy issues across the East Asia and Pacific region.